Encyclopedia Brown solves them all - Sobol, Donald J., 1924-; Shortall, Leonard W. (New York : Lodestar, 1968)
The town's ten-year-old walking encyclopedia again solves ten neighborhood mysteries. The final solutions to the cases are at the back of the book, giving readers a chance to compare their sleuthing skill to that of Encyclopedia Brown.
3.1
3-6
3-6
620
Keywords: Mystery and detective stories; Mystery fiction